GE_GERICHTE P/10445/2018 vom 25. April 2022 - GE Cour de justice (2022)
EXPULSION(DROIT PÉNAL);CAS DE RIGUEUR;TENTATIVE SIMPLE;MEURTRE;LÉSION CORPORELLE SIMPLE;CHANTAGE;DEVOIR D'ASSISTANCE(FAMILLE);INJURE;CONTRAINTE SEXUELLE;VIOL;VIOLENCE CONTRE LES AUTORITÉS | CP.123.ch1; CP.66a.al1; CP.66a.al2; CEDH.8.par1; CP.111; CP.22; CP.156.al1; CP.177.al1; CP.189.al1; CP.190.al1; CP.285